An Antibacterial Potential of Cerium Oxide Nanoparticles against Mycobacterium tuberculosis: A Novel Approach for Tuberculosis Treatment - Noonari, Shoukat Ali; Gul, Mahnoor; Ali, Jabir; Khan, Hassan Ali; Mustafa, Fahim (The Nucleus, 2025)
This study investigated the antibacterial effects of cerium oxide nanoparticles (CON) on Mycobacterium tuberculosis. Cerium oxide nanoparticles were synthesised using a microwave-induced technique and characterized by Scanning Electron Microscopy. Results indicated that an increase in synthesis time led to a reduction in nanoparticle size, demonstrating that the duration of the synthesis process influenced particle size. Additionally, the antibacterial activity of CON particles was found to be size-dependent. In a disc diffusion assay, cerium oxide nanoparticles enhanced the efficacy of antibacterial agents, significantly improving the effectiveness against Terivid, Amikin, Grasil, Velosef, Spraxin, and Ceftriaxone against Mycobacterium tuberculosis.